2016
DOI: 10.18632/oncotarget.10068
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of CD40L with CD70 or OX40L increases B-cell viability and antitumor efficacy

Abstract: Activated B-cells are a promising alternative source of antigen-presenting cells. They can generally be obtained in sufficient numbers for clinical use, but in most instances produce weak immune responses and therapeutic effects that are suboptimal for use in therapeutic cancer vaccines. To improve the immunogenic potency and therapeutic efficacy of B-cell-based vaccines, ex vivo-activated B-cells were transduced with recombinant lentiviruses in order to express additional costimulatory ligands—CD40L, CD70, OX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
1
8
2
Order By: Relevance
“…Meanwhile, the productions of IFN‐γ and TNF‐α were downregulated in the 4‐1BBL+ B cell group, indicating a negative regulatory role for cellular immunity. Interestingly, our data were not consistent with other studies, in which 4‐1BBL+ B cells could induce GrB+ CD8+ T cells and increase the proliferation of antigen‐specific CD8+ T cells . However, in our study, the 4‐1BBL+ B cells could increase cytokine secretion of IL‐2, IL‐4, and IL‐6.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the productions of IFN‐γ and TNF‐α were downregulated in the 4‐1BBL+ B cell group, indicating a negative regulatory role for cellular immunity. Interestingly, our data were not consistent with other studies, in which 4‐1BBL+ B cells could induce GrB+ CD8+ T cells and increase the proliferation of antigen‐specific CD8+ T cells . However, in our study, the 4‐1BBL+ B cells could increase cytokine secretion of IL‐2, IL‐4, and IL‐6.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, our data were not consistent with other studies, in which 4-1BBL+ B cells could induce GrB+ CD8+ T cells and increase the proliferation of antigen-specific CD8+ T cells. 17,37 However, in our study,…”
Section: Discussioncontrasting
confidence: 63%
“…It has been reported that PD-L1 is widely expressed on APCs such as macrophages, DCs, and B cells, and upregulated in response to inflammatory stimuli [27]. We and other have also shown that PD-1/PD-L1 blockade prevents exhaustion of tumor-reactive T cells in several malignancies, augmenting effector function and longevity of antigen-specific T cells at the tumor site [8,28,29]. A previous report demonstrated PD-L1 expression on murine bone marrow-derived DCs and that blockade of PD-1/PD-L1 interaction enhanced the number of T cells infiltrating the tumor and augmented longevity of tumor-reactive T cells in vivo [30].…”
Section: Discussionsupporting
confidence: 54%
“…For some time, numerous groups including us have explored to identify reliable autologous APC sources as an alternative for DC-based immunotherapy. Several studies have demonstrated that ex vivo –activated B cells using inflammatory cytokines, CD40L, and Toll-like receptor ligands possess a great ability to prime and expand antigen-specific T cells, resulting in in vivo therapeutic antitumor immunity [ 8 - 10 ]. In other reports, B cells genetically modified to express the costimulatory molecules, and B cells loaded with α-galactosylceramide have synergistically amplified T-cell proliferation as efficiently as DCs in vitro and induced a wide range of adaptive immunity against tumor cells [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…[67][68][69][70][71] The most relevant receptors in this setting are CD27, [72][73][74] CD28, [75][76][77] CD40, [78][79][80][81][82] TNF receptor superfamily, member 4 (TNFRSF4; best known as OX40), [83][84][85] TNF receptor superfamily member 9 (TNFRSF9; best known as CD137 or 4-1BB), [86][87][88][89] TNF receptor superfamily member 18 (TNFRSF18; best known as GITR), [90][91][92] and inducible T-cell costimulatory (ICOS). [93][94][95][96][97] The natural ligand for CD27 is CD70, 74,[98][99][100][101][102] CD28 is activated by CD80 and CD86 (hence sharing ligand specificity with CTLA4), 41,[103][104][105][106] while CD40 is the receptor for CD40 ligand (CD40LG), [107][108][109] OX40 for TNF superfamily member 4 (TNFSF4; best known as OX40L), [110]…”
Section: Introductionmentioning
confidence: 99%